PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION (LSQ) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIIISMPN 27 PADANG TAHUN PELAJARAN 2012/2013 - Yuwandra, Reza; Rismen, Sefna; Harisman, Yulyanti (Pendidikan Matematika, 2013)
The research was motivated by the studentâs comprehension of math concept and Â interes to ask orally are still low at SMPN 27 of Padang. This research aims to determine the studentâs comprehension of math concept that apply active learning strategies Learning Starts With a Question (LSQ) type better than studentâs comprehension of math concept that apply conventional learning in class VIII SMPN 27 Â of Padang. The type of research is experimental by using Randomized Control Group Only Design. The instrumen was used is end test by comprehension of math. The data analysis technique used is T-Test one part. The result of hypothesis test obtained T-Value is 2,12, it is bigger than T-table that is 1,645, then the hypothesis in this research received. In conclusion, studentsâs comprehension of math concept that apply active learning strategies Learning Starts With a Question (LSQ) type better than studentâs comprehension of math concept that apply conventional learning at class VIII SMPN 27 of Padang.Â